Effect of minimalist footwear on running efficiency: A randomized crossover trial - Gillinov, S. M.; Laux, S.; Kuivila, T.; Hass, D.; Joy, S. M. (Sports Health: A Multidisciplinary Approach, 2015)
Background: Although minimalist footwear is increasingly popular among runners, claims that minimalist footwear enhances running biomechanics and efficiency are controversial.